How are the new wave of Chinese researchers shaping up in scholarly communication terms? - Xu, Jie; Chen, Dianyun; He, Chen; Zeng, Yuanxiang; Nicholas, David; Wang, Zixian (Malaysian Journal of Library and Information Science, 2020)
The study investigates the attitudes and practices of Chinese early career researchers (ECRs) in regard to all scholarly aspects, providing the findings in the context of the academic assessment policies change in China over the last decade. The data were gathered by means of an online questionnaire survey, which obtained 263 Chinese ECRs’ responses. The main conclusions are: (a) journal-based indicators (e.g. journal reputation, Journal Impact Factor, Science Citation Index, etc.) are crucial when Chinese ECRs read and publish; (b) assessment policy plays a vital role when Chinese ECRs decide where to publish; (c) open access and open data have been widely recognized and warmly welcomed by Chinese ECRs, however, they will only publish in open access journals and open their research data if they get rewarded by the evaluation system; (d) most Chinese ECRs had good experience of peer review and they are in favor of double blind peer review; (e) Chinese ECRs are heavy users of social media, they are sophisticated in finding scholarly information online and communicating with peers and colleagues with social media tools.